1994
DOI: 10.1210/jcem.79.4.7962300
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis activation and stimulation of systemic vasopressin secretion by recombinant interleukin-6 in humans: potential implications for the syndrome of inappropriate vasopressin secretion.

Abstract: We recently demonstrated that sc administered interleukin-6 (IL-6) strongly stimulates the human hypothalamic-pituitary-adrenal (HPA) axis, with mild toxicity and no hypotensive effects. In this study, we evaluated the response of the human HPA axis to escalating iv doses of recombinant IL-6 in six patients with cancer and good performance status who received daily, every 8 h, three equal doses of 0.3-30 micrograms/kg IL-6. The plasma levels of IL-6 assayed by a specific enzyme-linked immunosorbent assay durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 28 publications
4
110
2
3
Order By: Relevance
“…The widespread and intensive inflammatory state involving the lungs, the liver, the kidneys, the intestines and the lymphatic ganglia induced to increase production of plasma prostaglandins and renin 9,29,33,34 . High serum levels of interleukin-6 have been detected in visceral leishmaniasis 3,32 and can act as a potent stimulus of the hypothalamicpituitary-adrenal axis and to arginine vasopressin(ADH) release too 14,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The widespread and intensive inflammatory state involving the lungs, the liver, the kidneys, the intestines and the lymphatic ganglia induced to increase production of plasma prostaglandins and renin 9,29,33,34 . High serum levels of interleukin-6 have been detected in visceral leishmaniasis 3,32 and can act as a potent stimulus of the hypothalamicpituitary-adrenal axis and to arginine vasopressin(ADH) release too 14,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between intracranial inflammation and ADH may be from increased levels of pro-inflammatory cytokines (i.e., IL-6, IL-1B), as well as of neutrophils, C-reactive protein and brain natriuretic peptide, all leading to increased release of ADH. A very small study done in 1994 including six patients with cancer showed that two hours after injection with IL-6, plasma ADH rose in all patients suggesting that this inflammatory cytokine may directly cause SIADH [15]. When inflammatory processes are responsible for SIADH, the syndrome usually will resolve after treatment of the infection [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in humans, IL-6 is an extremely potent activator of the axis and lacks the vascular leak-promoting and hypotensive side effects of the other two inflammatory cytokines. [110,111] The elevations in ACTH and cortisol levels attained by IL-6 are well above those observed with maximal stimulatory doses of CRH, suggesting that parvocellular AVP and other ACTH secretagogues are also recruited by this cytokine. At high doses, IL-6 also stimulates peripheral elevations of AVP, presumably as a result of a stimulatory effect on magnocellular AVP-secreting neurons.…”
Section: Stress System: Immune System Interactions Effects Of the Immmentioning
confidence: 97%
“…At high doses, IL-6 also stimulates peripheral elevations of AVP, presumably as a result of a stimulatory effect on magnocellular AVP-secreting neurons. [111] This suggests that IL-6 may be involved in the genesis of the syndrome of inappropriate antidiuretic hormone secretion, which is observed during the course of infectious or inflammatory disease or during trauma.…”
Section: Stress System: Immune System Interactions Effects Of the Immmentioning
confidence: 99%
See 1 more Smart Citation